Current Topics in Colorectal Surgery - Camilleri-Brennan, John (IntechOpen, 2023)
Surgery for colorectal disease, especially that involving minimal-access techniques, continues to evolve at a fast pace. This book provides a comprehensive and current overview of some specialist areas in this field. Chapters discuss colorectal cancer, including information on anatomy, investigations, and treatment. Other topics addressed include the pathophysiology and management of benign colorectal disease, fistula-in-ano, and inflammatory bowel disease. This book is an invaluable resource for physicians, surgeons, nurses, and allied healthcare professionals.